Data on the number and frequency of scientific literature citations for established medulloblastoma cell lines - Ivanov, D.P.; Walker, D.A.; Coyle, B.; Grabowska, A.M. (Elsevier, 2016)
This article collates information about the number of scientific articles mentioning each of the established medulloblastoma cell lines, derived through a systematic search of Web of Science, Scopus and Google Scholar in 2016. The data for each cell line have been presented as raw number of citations, percentage share of the total citations for each search engine and as an average percentage between the three search engines. In order to correct for the time since each cell line has been in use, the raw citation data have also been divided by the number of years since the derivation of each cell line. This is a supporting article for a review of in vitro models of medulloblastoma published in “in vitro models of medulloblastoma: choosing the right tool for the job” (D.P. Ivanov, D.A. Walker, B. Coyle, A.M. Grabowska, 2016) [1].